COST OF CREDIT IN CREDIT CARDS - Avelino Sánchez, Esteban Marino (2011)
It is important to note that credit card is a small loan, which makes use through the issuance of a custom plastic card has a magnetic strip and a number of relief. It serves as a means of payment for purchases and deferring payments for several months to get credit and pay off other debts. Credit card replaces cash, purchases are made during the period are accumulated in a monthly balance and debited to the card holder. Credit cards are used to obtain loans of small amounts until the card limit without prior approval, the money deferred interest incurred in a card. Credit cards are also used, wrongly, to cancel debts, there are better solutions to achieve the same purpose: the other forms of credit, less costly.